Desain Dinding Penahan Tanah pada Lereng Tidak Stabil Berbasis Analisis Numerik - Athaya Zhafirah; Rudy Febrijanto; Arby Muhyi Munawar (Jurnal Konstruksi, 2025)
A landslide occurred in Pananjung Village, Pamulihan District, Garut Regency, blocking the main road access in January 2024. The primary causes of slope instability were steep terrain and poor soil conditions. This study aims to analyze slope stability in the landslide area using a cantilever-type retaining wall as reinforcement. The study site is located in Pananjung Village, Pamulihan District, Garut Regency. The Bishop method was employed in the slope stability analysis, based on laboratory test results of the soil’s physical and mechanical properties. The tested parameters included water content, specific gravity, grain size distribution, and direct shear strength. The analysis was conducted both manually and using GeoStudio and Plaxis 2D software. The results indicate that the safety factor (FK) of the natural slope was below the safe threshold (FK < 1.5). After reinforcement with a retaining wall, the FK value increased beyond the safety limit, indicating a stable slope condition. The retaining wall design was developed based on an analysis of acting forces, considering stability against sliding, overturning, and bearing capacity. This study provides a practical contribution to landslide mitigation through a geotechnical approach based on numerical analysis. The findings can also serve as a technical reference for landslide risk mitigation in disaster-prone areas, offering a technical foundation for slope stabilization through the design of retaining walls grounded in numerical analysis.